My ballet book - Castle, Kate (New York DK Pub, 1998)
Introduces the world of ballet and presents its notable stories, dancers, techniques, and routines
Includes index
4
Keywords: Ballet dancing -- Juvenile literature; Ballet -- Juvenile literature; Ballet dancing; Ballet